Effects of Astragaloside IV on treatment of breast cancer cells execute possibly through regulation of Nrf2 via PI3K/AKT/mTOR signaling pathway. Issue 11 (18th September 2019) - Zhang, Xiao‐Qing; Yao, Chang; Bian, Wei‐He; Chen, Xu; Xue, Jing‐Xian; Zhu, Zhi‐Yuan; Ying, Yu; Xu, Yan Lei; Wang, Cong
Abstract: Traditional Chinese medicine (TCM) has from ancient times been applied in China for the treatment of breast cancer with its own unique theoretical system. Sanhuang decoction composed of astragalus membranaceus, prepared rhubarb, and rhizoma curcumae longae has traditionally been used for antioxidant stress, inflammatory reaction, and angiogenesis. However, the role and mechanism of Sanhuang decoction in breast cancer remains unknown. The present study demonstrated the antitumor activity of Sanhuang decoction against breast cancer xenografts in nude mice. Notably, Sanhuang decoction promoted severe necrosis and induced cell death. In addition, Sanhuang decoction obviously regulated the inflammation and oxidative stress. Despite these, Sanhuang decoction could increase the expression of Nrf2. Moreover, si‐Nrf2 exhibited the opposite effects compared with the Sanhuang decoction treatment group and reversed the antibreast cancer role of Sanhuang decoction. Further, Sanhuang decoction remarkably suppressed the expression of PI3K/AKT/mTOR signaling pathway. Taken together, Sanhuang decoction was firstly evaluated to possess potent antibreast cancer effect in vivo through regulation of inflammation and oxidative stress accomplished by up‐regulation of Nrf2 via PI3K/AKT/mTOR signaling pathway and Sanhuang decoction might be a powerful candidate formula for antibreast cancer. Abstract : Astragaloside IV had antitumor effects via regulation Nrf2 in vivo.